Nanostructured Lipid Systems as a Strategy to Improve the in Vitro Cytotoxicity of Ruthenium(II) Compounds - Freitas, Eduardo Sinesio de [UNESP]; Silva, Patricia Bento da [UNESP]; Chorilli, Marlus [UNESP]; Batista, Alzir Azevedo; Lopes, Erica de Oliveira [UNESP]; Silva, Monize Martins da; Leite, Clarice Queico Fujimura [UNESP]; Pavan, Fernando Rogério [UNESP] (Mdpi Ag, 2014)
Tuberculosis is an ancient disease that is still present as a global public health problem. Our group has been investigating new molecules with anti-TB activity. In this context, inorganic chemistry has been a quite promising source of such molecules, with excellent results seen with ruthenium compounds. Nanostructured lipid systems may potentiate the action of drugs by reducing the required dosage and side effects and improving the antimicrobial effects. The aim of this study was to develop a nanostructured lipid system and then characterize and apply these encapsulated compounds (SCARs 1, 2 and 4) with the goal of improving their activity by decreasing the Minimum Inhibitory Concentration (MIC90) and reducing the cytotoxicity (IC50). The nanostructured system was composed of 10% phase oil (cholesterol), 10% surfactant (soy oleate, soy phosphatidylcholine and Eumulgin (R)) and 80% aqueous phase (phosphate buffer pH = 7.4). Good activity against Mycobacterium tuberculosis was maintained after the incorporation of the compounds into the nanostructured lipid system, while the cytotoxicity decreased dramatically, in some cases up to 20 times less toxic than the unencapsulated drug.
Keywords: ruthenium complexes; tuberculosis; nanostructured lipid systems